Reduced asthma symptoms with n-3 fatty acid ingestion are related to 5-series leukotriene production - Broughton, KS; Johnson, CS; Pace, BK; Liebman, M; Kleppinger, KM (The American journal of clinical nutrition, 1997)
Asthma may respond to dietary modification, thereby reducing the need for pharmacologic agents. This study determined the effectiveness of n-3 polyunsaturated fatty acid (PUFA) ingestion in ameliorating methacholine-induced respiratory distress in an asthmatic population. The ability of urinary leukotriene excretion to predict efficacy of n-3 PUFA ingestion was assessed. After n-3 PUFAs in ratios to n-6 PUFAs of 0.1:1 and 0.5:1 were ingested sequentially for 1 mo each; patient respiratory indexes were assessed after each treatment. Forced vital capacity (FVC), forced expiratory volume for 1 s (FEV1), peak expiratory flow (PEF), and forced expiratory flow 25–75% (FEF 25–75) were measured along with weekly 24-h urinary leukotriene concentrations. With low n-3 PUFA ingestion, methacholine-induced respiratory distress increased. With high n-3 PUFA ingestion, alterations in urinary 5-series leukotriene excretion predicted treatment efficacy. Elevated n-3 PUFA ingestion resulted in a positive methacholine bronchoprovocation dose change in > 40% of the test subjects (responders). The provocative dose to cause a 20% reduction (PD20) in FEV1, FVC, PEF, and FEF25-75 values could not be calculated because of a lack of significant respiratory reduction. Conversely, elevated n-3 PUFA ingestion caused some of the patients (nonresponders) to further lose respiratory capacity. Five-series leukotriene excretion with high n-3 PUFA ingestion was significantly greater for responders than for nonresponders. A urinary ratio of 4-series to 5-series leukotrienes < 1, induced by n-3 PUFA ingestion, may predict respiratory benefit.